Memediasi masa lalu spektrum arkeologi dan pariwisata (Makassar Kerja sama Balai Arkeologi Makassar dengan Lembaga Penerbitan Universitas Hasanuddin, 2001)
Potentiality of archaeological remains and tourism in Sulawesi Selatan and Sulawesi Tenggara Provinces; collection of articles.
ASP-307g, donated by Victor J. Paz, Ph.d
Keywords: Archaeology -- Indonesia -- Sulawesi Selatan; Archaeology -- Indonesia -- Sulawesi Tengara; Tourism -- Indonesia -- Sulawesi Selatan; Tourism -- Indonesia -- Sulawesi Tenggara; Sulawesi Selatan (Indonesia) -- Antiquities; Sulawesi Tenggara (Indonesia) -- Antiquities